Hubungan Kegiatan Seni Rupa dengan Kemampuan Berfikir Kreatif Anak Usia Dini - Elva M. Sumirat; Cahaya Putri Yunus; Aprilia Lahati; Siti Aisa Moha; Apni Indah K. Ajun; Sri Rahayu D. Kanoli (Jurnal Pendidikan Anak Usia Dini dan Kewarganegaraan, 2026)
This study aims to determine the relationship between art activities and creative thinking abilities in early childhood. The research employed a quantitative method with a descriptive correlational approach. A total of 30 parents and teachers were selected as respondents through purposive sampling techniques. Data were collected using structured observation sheets and five-point Likert scale questionnaires, then analyzed using the Pearson Product Moment correlation test. The results showed that children's art skills were mostly in the good category with the highest percentage of 33.3%, while children's creative thinking abilities were in the creative category with the highest percentage of 33.3%. The correlation analysis yielded a value of r = 0.81, indicating a very strong positive relationship between art activities and creative thinking abilities in early childhood. These findings suggest that the better children's involvement in art activities, the higher their creative thinking abilities. The results of this study emphasize the importance of implementing planned and continuous art activities as a strategy to optimally develop creative thinking abilities in early childhood.